1970
DOI: 10.1063/1.1674048
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of NO2 Studied by Photoelectron and Vacuum-uv Spectroscopy and Gaussian Orbital Calculations

Abstract: The ionization potentials of NO2 up to 28 eV have been measured using He i and He ii high-resolution photoelectron spectroscopy. The assignment of the ionized levels below 16 eV is straightforward, including the singlet–triplet splittings, and allows us to assign Rydberg series in the vacuum uv leading to the first five ionization potentials. Above 16 eV the spectrum is complicated by the absence of obvious singlet–triplet splittings. The assignments we propose fit in with a coherent scheme for the molecular-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(37 citation statements)
references
References 21 publications
4
33
0
Order By: Relevance
“…A C H T U N G T R E N N U N G (6a 1 ) 1 . We think that the photoelectron spectrum studies of Brundle et al [1] and of Baltzer et al [2] are important in this field.…”
Section: A C H T U N G T R E N N U N G (1a 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…A C H T U N G T R E N N U N G (6a 1 ) 1 . We think that the photoelectron spectrum studies of Brundle et al [1] and of Baltzer et al [2] are important in this field.…”
Section: A C H T U N G T R E N N U N G (1a 2 )mentioning
confidence: 99%
“…Extensive experimental studies on the electronic states and photodissociation of the NO 2 + ion have been reported in the literature. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] For studying the electronic states of the NO 2 + ion, several experimental groups [1][2][3][4] investigated the photoelectron spectrum of the NO 2 molecule, which has a doublet ground 2 A 1 state with an electronic configuration of …A C H T U N G T R E N N U N G (3b 2 ) 2 …”
Section: Introductionmentioning
confidence: 99%
“…At the low temperature a long lived complex is formed so that sufficient curve crossing occur to allow the complex to exit in an exothermic channel NO + ('S) + 0( 3 S, 1 D,'P) At higher temperatures (T>300K) the complex is not being formed and the process is a direct one appearing to have an endothermic threshold. This has been rationalized by Ferguson [31] to be a consequence of the correlation of 0 + ( 4 S) and NO ( 2 7t) with the excited states 3 Ai, 3 Bj of N0 2 + which lie slightly above the reactants in energy [32]. The reaction does not i occur via non-adiabatic electron jump due to the low Frank-Condom factor.…”
Section: + + Nomentioning
confidence: 97%
“…V WSR dC/dt = Z{(dm/dt)j Cj /p} -C QWSR [28] where the summation is over all (32) A numerical scheme to calculate the transient response of the jet ring according to Eqns. [27] and [29] was implemented in the form of an EXCEL™ spreadsheet.…”
Section: -26mentioning
confidence: 99%
See 1 more Smart Citation